Tantangan Dan Peran Hukum UMKMKecamatan Kedung Waringin Dalam Bisnis Digital - Ergo Nurpatria Kurniawan; Joni Heruwanta; Muh Ali Maskuri; Surya Bintarti; Taufiq Rachman (LPPM STEBIS YPII, 2024)
Facing the current challenges and opportunities, of course UMKM must move dynamically and quickly in managing their business and understanding the legality of the law. Changes and shifts in digital tastes and culture have created economic disruption in many business sectors, although on the other hand they have created new business opportunities. The existence of UMKM within the framework of the national economy has a significant economic impact in providing economic contributions and driving the real sector and empowering the community. UMKM have to move from the conventional level (offline) to the digital level (online), because now it must be understood that the digital era is impossible to avoid. Yuswohadi, an expert, revealed that if they want to survive, UMKM must be able to optimize the benefits of digital development. The result of this community service program is that activities run smoothly, according to the schedule of events and it is recommended that there will be further training for Bekasi District UMKM.